UTILIZING FIBER MESH AND NYLON ROPE AS NON-STEEL REINFORCEMENT FOR SANDWICH CONCRETE PLATE PRECAST IN COASTAL AREA STRUCTURES - Elvira, Elvira (Fakultas Teknik Universitas Tanjungpura, 2024)
Reinforced concrete, a popular construction choice, is often selected due to the limited availability of materials like wood and increased familiarity with concrete. However, coastal structures using steel bars in reinforced concrete usually face corrosion issues. Corrosion can be mitigated by increasing concrete compressive strength and enlarging the concrete cover to protect the steel from saltwater. These measures are challenging for small structures due to the small dimensions of columns, beams, and plates, making thick concrete covers difficult. Additionally, small structures are often built manually or semi-manually, complicating the achievement of higher compressive strength and watertightness. However, there is hope. Researchers have developed reinforced concrete with non-metal reinforcement, such as fiber mesh and nylon rope, and combined regular and lightweight concrete to reduce dead loads, creating a sandwich concrete slab. Test results show that the slab has sufficient strength for light construction, with a strong bond between mortar and foam concrete. Although fiber mesh and nylon rope do not yet increase the slab's flexural strength, nylon rope prevents brittle failure. This promising research paves the way for further studies and potential improvements in the future.